Study on the production and marketing of sunflower seeds worldwide in the period 2015-2020 - Elena Soare; Irina Chiurciu; Livia David; Aurelia Balan; Carina Dobre; Adina Iorga (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This study highlights important aspects regarding the production and marketing of sunflower seeds worldwide for the period 2015-2020. In order to achieve this study, a series of indicators specific to the sector of production and marketing of sunflower seeds were analyzed, such as: the area cultivated worldwide with sunflower; the production of sunflower seeds achieved worldwide; the average production per hectare of sunflower; the imports and exports of sunflower seeds worldwide. Sunflowers are cultivated on all continents, but on different surfaces. Europe is the leader of the ranking at continental level, regarding, on the one hand, the areas cultivated with sunflower, and on the other hand, the production obtained for sunflower seeds. Sunflower seeds have a number of uses, which places them in the area of the most important oilseeds crops. Nowadays, worldwide, the production and marketing of sunflower seeds is given a special importance. The statistical data presented and analyzed in the study were taken from the FAOSTAT website.
Keywords: Q11; Q13; Q17; 330; areas cultivated with sunflower; average production per hectare of sunflower; imports and exports ofsunflower seeds worldwide